The developmental, dimensional and diagnostic interview (3di): a novel computerized assessment for autism spectrum disorders. - Skuse, D; Warrington, R; Bishop, D; Chowdhury, U; Lau, J; Mandy, W; Place, M (2004)
OBJECTIVE: Autism is a diagnostic spectrum of variable severity, with significant comorbidity. No existing standardized interview measures autistic features dimensionally. The authors aimed to develop a parental autism interview that could be administered to unselected clinical and general population samples that measures both symptom intensity and comorbidity across the full range of the autistic spectrum. METHOD: A computerized procedure was devised for administration by trained interviewers that generates symptom and diagnostic profiles for both autism and non-autistic conditions. Test-retest reliability and interrater reliability were assessed in unselected clinical (n = 50) and nonclinical (n = 30) populations. Concurrent validity (n = 120), discriminant validity (n = 120), and criterion validity (n = 29) were evaluated in autistic spectrum and non-autistic patients. RESULTS: Test-retest and interrater reliabilities were excellent (most intraclass correlation coefficients > 0.9). Concurrent validity (agreement with independent clinician formulation) was very good (mean kappa = 0.74). Criterion validity, a comparison with the Autism Diagnostic Interview, was excellent. Discrimination between autistic spectrum versus non-autistic subjects was almost perfect (sensitivity 1.0; specificity > 0.97). CONCLUSIONS: The Developmental, Dimensional and Diagnostic Interview (3di) provides an efficient and accurate means of assessing, in dimensional terms, the presence of autistic symptoms in both clinical and normal populations. It offers novel opportunities for those engaged in research and clinical practice.